OBSTACLES TO UTILIZATION OF DENTAL SERVICES IN KARACHI, PAKISTAN - Aliuddin, Azam Muhammad; Ali, Jabeen Zafar; Sheikh, Abubakar; Rashid, Saqib (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the different views of the people, regarding dental health, based on gender and level of education. Study Design: Cross sectional study. Place and Duration of Study: OPD of Fatima Jinnah Dental College and Hospital, Karachi, from Jan to Jun 2018. Methodology: A total of 500 patients were seen in the Diagnosis Department of the hospital. A structured questionnaire was devised to obtain adequate information from the participants. The study was focused on young and middle aged individuals to acquire an analogous output of the society. Ages between 20-35 and 36-60 were preferred. Results: Out of 500 responses, 265 participants belonged to the younger age group of 20-35 years (53%). In this, 29.2% of the patients stated that when they experience any dental problem or pain they prefer going to a medical practitioner as compared to a dentist (16.4%). A high percentage (42.8%) believed in self-medication and occasionally practice home remedies for such problems. In 19.2% said that they feared the dental treatment hence were not willing to visit the dentist, owing to unpleasant dental experiences previously (16.6%) and many facing difficulties in reaching the dental facility (16.4%) or having to travel far away for treatment (13.8%). Conclusion: Routine dental checkups have been limited by many different elements, the most common ones being dental fear, expenses of overall treatment, socioeconomic factors and the constant feeling of not „needing‟ dental care. Self-medication and home remedies for dental problems have also been highly reported along with the practice of visiting a medical practitioner for dental issues.